Sedimentology and stratigraphy of the Carboniferous Donegal Basin - Ní Bhroin, Charlotte (Trinity College (Dublin, Ireland). Department of Geology, 2000)
The Dinantian onshore Donegal Basin is situated at the northerly exposed margin of the Northwest Carboniferous Basin of Ireland. Subsidence patterns in the Northwest basin were strongly controlled by an existing template of major NE/SW trending Caledonian faults. The Donegal Basin exposes a sequence of rocks, which were deposited in a range of environments. These comprise fluvial, tidally influenced, marginal marine and shelf to open marine areas. As this area lay close to or on the palaeo-shoreline during Viséan, it is an ideal place to study relative changes in base level. This study has outlined the Donegal succession which indicates an overall transgressive sequence from Tournaisian to Arundian (and possibly Holkerian) times. During the Arundian, a regional regression affected large areas of northern Ireland, which is also recognised in south Donegal. It has been demonstrated within this work that the events causing these changes can be temporally constrained using information gained from field mapping and foraminiferal biostratigraphy.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin